Facilitating or hindering elements of the Care Transition process: na integrative review (Research, Society and Development, 2021)
Objective: to summarize in the literature the elements that facilitate or hinder the transition of care from adult users from the perspective of nurses and/or users of surgical hospitalization services to the home or Primary Health Care. Materials and method: this is a integrative literature review. The search took place in January 2021, in the Latin American and Caribbean Literature in Health Sciences, National Library of Medicine/National Institutes of Health and SciVerse Scopus databases. For the selection of studies, the classification of levels of evidence was used. Results: A total of 731 productions were located, of which 23 made up the corpus of the study. The elements identified in the literature as facilitating or hindering the care transition process were: conducting discharge planning, outpatient follow-up, monitoring and managing symptoms after discharge, education and promotion of self-management, medication safety, organization, clarity, availability , timely information, communication and coordination of care between members of the health team. Conclusions: studies like this one are essential to give visibility to nurses in the transition of care, and to reflect on the importance of articulated work in networks at different levels of health care.